The role of ZNRF3 in testis determination - Harris, A (2017)
In mammals, the presence or absence of SRY primarily determines whether the gonad will develop as a testis or an ovary – a process known as sex determination. Downstream of SRY, the testis and ovarian pathways diverge and mutually antagonise each other to ensure a robust switch in gonadal fate. One such interaction is well characterised in mice, between the ovary-promoting gene, Wnt4 and the testis-determining gene, Fgf9. The mutual repression of these two genes has recently been shown to be crucial for mouse sex determination. However, there is currently little evidence for how this interaction between the male and female pathways, and others required for sex determination, may be controlled at the molecular level. Differences/disorders of sex development (DSDs) are a group of rare human conditions in which chromosomal and anatomical sex are discordant. Exome screens of DSD patients exhibiting gonadal dysgenesis can be used to identify candidate genes. In one such screen, 2 independent mutations were found in ZNRF3. ZNRF3 is a WNT-signalling antagonist which functions by downregulating the number of Frizzled receptors available on the plasma membrane. WNT4 is expressed in pregranulosa cells and plays a key role in ovarian development through promotion of beta-catenin-dependent gene transcription. This thesis demonstrates that Znrf3 plays an important role in testis determination in the mouse. Znrf3 is required to suppress the ovarian-pathway, and when removed from the testis causes partial or full XY sex reversal associated with ectopic activation of WNT/ beta-catenin signaling. Moreover, use of a sensitized genetic background allows generation of sex-reversed XY female mice carrying a single copy of a Znrf3 null allele. ZNRF3 may therefore play a key role in mediating the mutually antagonistic interactions between the testis and ovarian pathways, in both mice and in humans.